Potentiometric determination of minoxidil in topical use pharmaceutical samples - de Sousa, Rogério Adelino; Cavalheiro, Éder Tadeu Gomes (Eclética Química, 2009)
A potentiometric titration method for the determination of minoxidil based on its redox reaction with K2Cr2O7 is described. The best results were observed using 1.00 x 10-3 mol L-1 K2Cr2O7 and 1.00 x 10-2 mol L-1 minoxidil solutions, and the minoxidil as titrant in 2.00 mol L-1 H2SO4 medium. The method was applied to commercial samples and compared with the results from a chromatographic procedure. Recoveries from 97.4 to 98.7 % were observed depending on the sample. Comparison with the chromatographic procedure reveled agreement within 90% confidence level.